Kinetic and oligomeric study of Leishmania braziliensis nicotinate/nicotinamide mononucleotide adenylyltransferase. Issue 4 (April 2020) - Contreras Rodríguez, Luis Ernesto; Ziegler, Mathias; Ramírez Hernández, María Helena
Abstract: Nicotinamide adenine dinucleotide (NAD) is an essential coenzyme involved in REDOX reactions and oxidative stress defense systems. Furthermore, NAD is used as substrate by proteins that regulate essential cellular functions as DNA repair, genetic, and signal transduction, among many others. NAD biosynthesis can be completed through the de novo and salvage pathways, which converge at the common step catalyzed by the nicotinate/nicotinamide mononucleotide adenylyltransferase (NMNAT EC: 2.7.7.1/18). Here, we report the kinetic characterization of the NMNAT of Leishmania braziliensis (LbNMNAT), one of the etiological agents of leishmaniasis, a relevant parasitic disease. The expression and homogeneous purification of the recombinant 6xHis-LbNMNAT protein was carried out and its kinetic study, which included analysis of K m, V max, K cat and the equilibrium constant ( K D ) for both the forward and reverse reactions, was completed. The oligomeric state of the recombinant 6xHis-LbNMNAT protein was studied through size exclusion chromatography. Our results indicated the highest and lowest K m values for ATP and NAD, respectively. According to the calculated K D, the pyrophosphorolytic cleavage of NAD is favored in vitro. Moreover, the recombinant 6xHis-LbNMNAT protein showed a monomeric state, although it exhibits a structural element involved in potential subunits interaction. Altogether, our results denote notable differences of the LbNMNAT protein in relation to the human orthologs HsNMNAT1-3. These differences constitute initial findings that have to be continued to finally propose the NMNAT as a promissory pharmacological target in L. braziliensis . Abstract : Microbiology; Biocomputational method; Leishmania; Enzyme kinetics; Chromatography; Biomolecules; Parasitology; Leishmania braziliensis; Nicotinate/nicotinamide mononucleotide adenylyltransferase (NMNAT); Nicotinamide adenine dinucleotide (NAD); Oligomeric states; Kinetic characterization.